Considerações sobre o desempenho político-eleitoral do Partido dos Trabalhadores em Minas Gerais, entre 1989 e 2002 - Marques, Angela Peralva Baumgratz (2005)
This research approaches the performance of the Workers Party (PT) at Minas Gerais Legislature. It evaluates both the behavior of candidates running for the office of State Deputy and the political strategies used by these candidates to secure popular support, covering the period from 1990 through 2002. The growing number of PT representatives in the Legislature was strongly influenced by the party migrating from a leftist-oriented policy to a middle-of-the-road position in the political spectrum. This change was caused by external pressure, which led the party to stay away from their leftist tendencies. As a result, the party no longer supported a revolutionary ideology and consequently embarked on a reformist practice. The party exerts a strict control over both the candidates’ political campaigns and the party’s deputies’ activities. Because of this, their deputies are also influenced by the general guidelines set up by PT’s national office. Considering that, based on their partyism ideology, they criticize clientelism and individualized attention, deputies are engaged in a process of building up their electorate bases and drawing near to organized movements, the party doesn’t break free from the peculiar nationwide political personalism. As we focus on PT representatives elected in Minas Gerais State during the years 1990 through 2002, we can determine that the Workers party doesn’t fit the so called catch-all model as it is permeated by a high degree of party loyalty, is deeply related to unions and social movements and their representatives do not use the party as an electing front.